Informal Settlement Characterization and Socio-Economic Vulnerability Assessment in Kolkata Metropolitan City, India - Banerjee, Shravani; Diksha, Diksha; Prasad, Alisha; Kumar, Amit (Geoplanning: Journal of Geomatics and Planning, 2024)
The study investigates the physical, social, and economic environment of the Kolkata Metropolitan Area (KMA) to elucidate the living conditions of informal settlements and its influence on the local environment using geoinformatics and multi-criteria decision making-analytical hierarchical process (MCDM-AHP). The informal settlements were delineated using high-resolution Google Earth imagery and generic ontology informal settlements. knowledge considering building characteristics, building density, locations of the dwelling units, and their characteristics. The study exhibits that most informal settlements were concentrated in the wards located in the eastern and central parts of the city. The neighborhood land-use functions of the major informal settlements indicated that the informal settlements were highly influenced by green space (R2=0.97), followed by water bodies (R2=0.74), unplanned settlement (R2=0.68) and planned settlement (R2=0.67) in KMA. In addition, the informal settlements were closely associated with very low relief zones (3m to 13m) followed by moderate relief zones (13-23m). The municipal ward-level analysis of the physical-socio-economic health conditions exhibited that most of the areas located in the low vulnerable zones (53.71 km2; primarily in southern, and eastern periphery), followed by very highly vulnerable zones (43.09 km2; primarily in central and northern parts). The study provides an insight into urban areas with special reference to informal settlements and necessitates the implication of effective policy for poverty alleviation. This study encourages the availability of real-time data that can improve mitigation activities in the event of a health disaster, such as SARS COVID-19 through methods for qualitative investigation of disadvantaged locations in Kolkata.